2013
DOI: 10.1039/c2em30785e
|View full text |Cite
|
Sign up to set email alerts
|

Levels and distribution of polybrominated diphenyl ethers in soil, sediment and dust samples collected from various electronic waste recycling sites within Guiyu town, southern China

Abstract: Electronic waste recycling operations in some parts of Asia are conducted using rudimentary techniques which result in workplace and environmental contamination with toxic metals and persistent organic pollutants. This study reports concentrations of 14 polybrominated diphenyl ethers (PBDEs), from tri- to deca-brominated, in 31 samples of soil, sediment, dust or ash collected in the vicinity of e-waste recycling sites in Guiyu (southeast China) which were engaged in common activities such as dismantling, shred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 28 publications
(27 reference statements)
3
21
1
Order By: Relevance
“…The levels of penta-BDEs in this study could be related to those reported by Yang et al (2013), in which the profiles of PBDE 4-6 were found to be similar to the commercial penta-BDE products (with trade name, DE-71 and Bromkal 70-5DE), thus implicating the use of these two products in electronic equipment. Similarly, the high levels of BDE 99, 100, 153 and 154 could be linked to debromination of BDE 209 ) as well as the influence of penta-and octa-BDE commercial formulations with known applications in printed circuit board components (Labunska et al 2013). Similarly, our results for tetra-through hexa-BDEs were in line with levels reported in indoor dust which were consistent with concentrations in human serum and milk of the US general population (Sjödin et al 2008).…”
Section: Levels Of Pbdessupporting
confidence: 90%
See 1 more Smart Citation
“…The levels of penta-BDEs in this study could be related to those reported by Yang et al (2013), in which the profiles of PBDE 4-6 were found to be similar to the commercial penta-BDE products (with trade name, DE-71 and Bromkal 70-5DE), thus implicating the use of these two products in electronic equipment. Similarly, the high levels of BDE 99, 100, 153 and 154 could be linked to debromination of BDE 209 ) as well as the influence of penta-and octa-BDE commercial formulations with known applications in printed circuit board components (Labunska et al 2013). Similarly, our results for tetra-through hexa-BDEs were in line with levels reported in indoor dust which were consistent with concentrations in human serum and milk of the US general population (Sjödin et al 2008).…”
Section: Levels Of Pbdessupporting
confidence: 90%
“…Generally, BDE congeners 209 and 99 were the most prevalent amongst the studied congeners (Fig. 2) The concentrations of PBDEs in this study were higher than levels reported in Guiyu, China (Leung et al 2011), in indoor dust from e-waste workshops, and also higher than levels reported by Tue et al (2013) in settled house dust around Vietnamese e-waste recycling sites, but several orders of magnitude lower than levels recently reported in indoor dust from e-waste recycling sites in Thailand and Southern China (Labunska et al 2013;Muenhor et al 2010). The levels of penta-BDEs in this study could be related to those reported by Yang et al (2013), in which the profiles of PBDE 4-6 were found to be similar to the commercial penta-BDE products (with trade name, DE-71 and Bromkal 70-5DE), thus implicating the use of these two products in electronic equipment.…”
Section: Levels Of Pbdescontrasting
confidence: 78%
“…''The Handbook of Environmental Chemistry'' identifies Guiyu as the largest and the second most polluted site in the world due to its informal recycling processes (acid extraction for metals, open burning of wires to get copper) [38]. Decreases in PBDE concentrations are observed with increasing distance from workshops in samples linked with acid processing of waste [39]. Similar results are found when family residences serve as workshops.…”
Section: Discussionsupporting
confidence: 70%
“…BFR containing or polyvinyl chloride (PVC) coated copper cables, provide optimal conditions for de novo formation of halogenated aromatic compounds, such as PCDD/Fs, its brominated equivalents PBDD/Fs, mixed brominated/chlorinated homologies (PXDD/Fs) and other dioxin-related compounds (DRCs) (Weber and Kuch, 2003;Hedman et al, 2005;Gullett et al, 2007;Duan et al, 2011;Hibbert and Ogunseitan, 2014). Due to uncontrolled combustion and thermal processing of e-waste, these POPs have been found in the air, bottom ash, dust, soil, water and sediment samples from EWRSs worldwide, partly in tremendous high concentrations (Li et al, 2007;Wong et al, 2007;Brigden et al, 2008;Liu et al, 2008;Ma et al, 2009aMa et al, , 2009bWen et al, 2009Wen et al, , 2011Ni et al, 2010;Tue et al, 2010b;Zhang et al, 2012b;Chan and Wong, 2013;Hu et al, 2013;Labunska et al, 2013;Ren et al, 2013;Wang et al, 2013;Hosoda et al, 2014;Xiao et al, 2014). The share of annual mass of e-waste derived PCDD/F in China alone is estimated to be in the range of several kilograms (Ni et al, 2010).…”
Section: Introductionmentioning
confidence: 96%